2017
DOI: 10.1371/journal.pone.0171170
|View full text |Cite
|
Sign up to set email alerts
|

The SLC6A3 gene possibly affects susceptibility to late-onset alcohol dependence but not specific personality traits in a Han Chinese population

Abstract: Dopaminergic dysfunction has an important role in the pathoetiology of alcohol dependence (AD). The purpose of this study was to determine whether the solute carrier family 6 member 3 (SLC6A3) gene (also known as the dopamine transporter DAT gene) was associated with AD, and whether variants in the SLC6A3 locus were associated with specific personality traits in patients with AD. Sixteen polymorphisms in SLC6A3 were analyzed using 637 patients with AD and 523 healthy controls. To reduce clinical heterogeneity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…In fact, novelty seeking is the characteristics of sensation‐seeking personality in humans, and higher novelty seeking would predict the initiation of drug use, subsequent compulsive use, and the risk to relapse . Our finding is consistent with previous substance‐related studies, including alcohol, amphetamine, cocaine, tobacco, and cannabis . In addition, our study found a negative correlation between NS score and age in patients with HD, implying that adolescents display higher levels of novelty seeking than do adults, and may have higher risk for developing substance dependence …”
Section: Discussionsupporting
confidence: 90%
“…In fact, novelty seeking is the characteristics of sensation‐seeking personality in humans, and higher novelty seeking would predict the initiation of drug use, subsequent compulsive use, and the risk to relapse . Our finding is consistent with previous substance‐related studies, including alcohol, amphetamine, cocaine, tobacco, and cannabis . In addition, our study found a negative correlation between NS score and age in patients with HD, implying that adolescents display higher levels of novelty seeking than do adults, and may have higher risk for developing substance dependence …”
Section: Discussionsupporting
confidence: 90%
“…It is well known that the SLC6A3 gene codes for the dopamine transporter; however, there is conflicting evidence regarding the transporter and its relation to substance dependence. [35][36][37][38][39] Some authors have proposed that these conflicting associations are due to the genetic position of the variants, since some are located in the first exons while others are in the 3'-UTR region, which affects either expression or proper transcription, hence the functional effect of the protein. 35 Our targeted sequencing approach was capable of detecting genetic variations across whole genes due to the fact that we included at least 50 bp of untranslated regions for sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39] Some authors have proposed that these conflicting associations are due to the genetic position of the variants, since some are located in the first exons while others are in the 3'-UTR region, which affects either expression or proper transcription, hence the functional effect of the protein. 35 Our targeted sequencing approach was capable of detecting genetic variations across whole genes due to the fact that we included at least 50 bp of untranslated regions for sequencing. The association between substance use and intron 6 of SLC6A3 has been reported to have a regulatory impact, promoted by the union of transcriptional repressor CTCF.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in the variable number of tandem repeats (VNTR) in the 3′ untranslated region of the SLC6A3 gene coding for the DA transporter (DAT) have been reported in both obesity , and drug addiction. DAT is important for maintaining dopaminergic tone via sequestering DA back into the presynaptic neuron. In vitro studies suggest that the SLC6A3 VNTR polymorphism influences gene expression and DAT availability.…”
Section: Polymorphisms In D2 Receptor and The Da Transportermentioning
confidence: 99%